Ryzykowne zachowania seksualne dzieci, młodzieży i młodych dorosłych w kontekście korzystania z technologii cyfrowych = Risk sexual behaviours of children, adolescents and young adults in the context of using digital technologies - Ronatowicz, Wojciech (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper is an in-depth analysis of risk behaviours of children and adolescents who use digital technologies. The author discusses the issue of child, adolescent and young adult sexuality in the context of using such media as the Internet or a mobile phone. The article includes a theoretical introduction concerning the use of digital media and presents the research on the subject.
Keywords: psychosexual development; children and adolescents; pornography; grooming; sexual abuse; cyberbullying; rozwój psychoseksualny; dzieci i młodzież; pornografia; uwodzenie; wykorzystywanie seksualne; cyberprzemoc